Pioneer Interviews, - Teakle, Thomas
Pioneer interviews conducted by Thomas Teakle's history class in the 1938-1939 school year. The student papers are not transcripts of interviews, but "pioneer stories" the students wrote after conducting the interviews. The interviews are with the following Spokane pioneers: Sjur Sjursen Berven, Jane Bigelow, Theolinda Pynn, J. Griffeth, Sam Griffith, Sam Glasgow, Edward F Kohlhauff, Jim Lefevere, Laura Mohr, Alonzo Murphy, James M. Penfield, E. I. Seehorn, Zack Stewart, Emma Tiffen, and Henry Tramm. The students names are given on the papers, but there is not information on the student. The pioneers talk about their arrival in Spokane (many in the 1880s), the 1889 fire, life in early Spokane and many talk about their contact with the local Indians.